Few‐Layer Graphdiyne Nanosheets Applied for Multiplexed Real‐Time DNA Detection. Issue 18 (10th March 2017) - Parvin, Nargish; Jin, Quan; Wei, Yanze; Yu, Ranbo; Zheng, Bing; Huang, Ling; Zhang, Ying; Wang, Lianhui; Zhang, Hua; Gao, Mingyuan; Zhao, Huijun; Hu, Wenping; et al.
Abstract : Despite recent progress in 2D nanomaterials‐based biosensing, it remains challenging to achieve sensitive and high selective detection. This study develops few‐layer graphdiyne (GD) nanosheets (NSs) that are used as novel sensing platforms for a variety of fluorophores real‐time detection of DNA with low background and high signal‐to‐noise ratio, which show a distinguished fluorescence quenching ability and different affinities toward single‐stranded DNA and double‐stranded DNA. Importantly, for the first time, a few‐layer GD NSs‐based multiplexed DNA sensor is developed. Abstract : Graphdiyne nanosheets (GD NSs) based multiplexed DNA detection through different routes . Route I: Dye‐labeled ssDNA with different fluorescence is first mixed with GD NSs result in completely quenching of the dyes. Then, in the presence of the target DNA (T1: ruby; T2: blue), the forming of dsDNA makes the release of dye‐labeled DNA from the surface of GD NSs result in the fluorescence recovery, finishing the detection; and Route II: Dye‐labeled ssDNA is first mixed with target DNA, after that GD NSs are added for the detection.